Comparative bioavailability of two irbesartan/hydrochlorothiazide tablet formulations in Indonesian healthy subjects - Sasongko, Lucy; Harahap, Yahdiana; Prasaja, Budi; Lusthom, Windy; Setiawan, Evy C; Meliala, Raria S; Lipin, L (Arzneimittelforschung, 2010)
The bioavailability of two 300 mg irbesartan (CAS 138402-11-6)/12.5 mg hydrochlorothiazide (CAS 58-93-5) tablet formulations was compared, using Co-Irvell® tablets as test formulation and the originator product as reference formulation.Twenty-four subjects were included in this single-dose, open-label, randomized two-way crossover study following an overnight fasting. A two-week wash-out period was applied. Blood samples were drawn up to 48 h following drug administrations. Irbesartan and hydrochlorothiazide plasma concentrations were determined by liquid chromatography-tandem mass spectrometry method with TurboIonSpray mode. Pharmacokinetic parameters AUC0–t, AUC0–∞, Cmax and t were determined and used for bioequivalence evaluation after log-transformation, whereas tmax ratios were evaluated non-parametrically.The estimated point and 90% confidence intervals (CI) for AUC0–t, AUC0–∞, Cmax and t for irbesartan were 97.74% (85.40–111.86%), 96.36% (83.25–111.55%), 103.30% (90.65–117.71%), 92.38% (82.68–103.21%) and for hydrochlorothiazide, 106.30% (97.72–115.63%), 106.28% (98.14–115.10%), 108.01% (95.48–122.18%), 105.52% (96.70–115.14%), respectively.These results indicated that the two formulations of irbesartan/hydrochlorothiazide were bioequivalent; therefore they may be prescribed interchangeably.
Keywords: Antihypertensives; Bioavailability; Bioequivalence; CAS 58-93-5; CAS 138402-11-6; Hydrochlorothiazide; Irbesartan